Inhibition of the Neuronal Calcium Sensor DREAM Modulates Presenilin-2 Endoproteolysis - Naranjo, Rocío; González, Paz; Lopez-Hurtado, Alejandro; Dopazo, Xosé M.; Mellström, Britt; Naranjo, José R. (Frontiers in Molecular Neuroscience, 2018)
Deregulated intracellular Ca2+ and protein homeostasis underlie synaptic dysfunction and are common features in neurodegenerative diseases. DREAM, also known as calsenilin or KChIP-3, is a multifunctional Ca2+ binding protein of the neuronal calcium sensor superfamily with specific functions through protein-DNA and protein-protein interactions. Small-molecules able to bind DREAM, like the anti-diabetic drug repaglinide, disrupt some of the interactions with other proteins and modulate DREAM activity on Kv4 channels or on the processing of activating transcription factor 6 (ATF6). Here, we show the interaction of endogenous DREAM and presenilin-2 (PS2) in mouse brain and, using DREAM deficient mice or transgenic mice overexpressing a dominant active DREAM mutant in the brain, we provide genetic evidence of the role of DREAM in the endoproteolysis of endogenous PS2. We show that repaglinide disrupts the interaction between DREAM and the C-terminal PS2 fragment (Ct-PS2) by coimmunoprecipitation assays. Exposure to sub-micromolar concentrations of repaglinide reduces the levels of Ct-PS2 fragment in N2a neuroblastoma cells. These results suggest that the interaction between DREAM and PS2 may represent a new target for modulation of PS2 processing, which could have therapeutic potential in AD treatment.